Characterization of papain-like isoenzymes from latex of Asclepias curassavica by molecular biology validated by proteomic approach - Obregón, Walter David (2009)
Latices from Asclepias spp are used in wound healing and the treatment of some digestive disorders. These pharmacological actions have been attributed to the presence of cysteine proteases in these milky latices. Asclepias curassavica (Asclepiadaceae), “scarlet milkweed” is a perennial subshrub native to South America. In the current paper we report a new approach directed at the selective biochemical and molecular characterization of asclepain cI (acI) and asclepain cII (acII), the enzymes responsible for the proteolytic activity of the scarlet milkweed latex. SDS-PAGE spots of both purified peptidases were digested with trypsin and Peptide Mass Fingerprints (PMFs) obtained showed no equivalent peptides. No identification was possible by MASCOT search due to the paucity of information concerning Asclepiadaceae latex cysteine proteinases available in databases. From total RNA extracted from latex samples, cDNA of both peptidases was obtained by RT-PCR using degenerate primers encoding Asclepiadaceae cysteine peptidase conserved domains. Theoretical PMFs of partial polypeptide sequences obtained by cloning (186 and 185 amino acids) were compared with empirical PMFs, confirming that the sequences of 186 and 185 amino acids correspond to acI and acII, respectively. N-terminal sequences of acI and acII, characterized by Edman sequencing, were overlapped with those coming from the cDNA to obtain the full-length sequence of both mature peptidases (212 and 211 residues respectively). Alignment and phylogenetic analysis confirmed that acI and acII belong to the subfamily C1A forming a new group of papain-like cysteine peptidases together with asclepain f from Asclepias fruticosa. We conclude that PMF could be adopted as an excellent tool to differentiate, in a fast and unequivocal way, peptidases with very similar physicochemical and functional properties, with advantages over other conventional methods (for instance enzyme kinetics) that are time consuming and afford less reliable results.